A conceptual model of the Amblyomma americanum life cycle in northeast Missouri. Issue 1 (23rd May 2013) - Bouzek, D. C.; Foré, S. A.; Bevell, J. G.; Kim, H.‐J.
ABSTRACT: The geographic distribution of Amblyomma americanum (the lone star tick) has increased as has its role as a pathogen vector. The objectives of this study were to determine seasonal activity patterns of each life stage of A. americanum in the northwestern part of the species range and the relationship of these activity patterns among life stages and degree days. Tick activity was monitored over four years since 2007 in a forest and old field habitat located in northeast Missouri. Every other week from February to December, ticks were collected using bait and drag methods. Autocorrelations demonstrated yearly seasonal patterns in each life stage and cross‐correlations between life stages depicted a relationship between activity at a life stage and the previous stage's activity. Cross‐correlations indicated that degree days were related to activity. These data indicated that A. americanum generally complete their life cycle in a minimum of two years in northeast Missouri, with overwintering occurring predominantly in the nymphal and adult stages. These data provide a baseline to compare the life cycle of A. americanum in northeast Missouri to populations in different parts of the species range or at different times in the region.